Nature and nurture in vitamin B12 deficiency - Zschocke, Johannes; Schindler, S.; Hoffmann, Georg F.; Albani, Michael (Archives of disease in childhood, 2002)
We report on a child in whom severe nutritional vitamin B12 deficiency was exacerbated by a genetic impairment of the folate cycle, causing reduced CSF concentrations of the methyl group donor 5-methyltetrahydrofolate. Some patients with vitamin B12 deficiency may benefit from high dose folic acid supplementation, even if plasma concentrations are high.